Disability Athlete Achievement Coaching Management - Hezron Alhim Dos Santos; Nukhrawi Nawir (Journal Management of Sport, 2023)
The study aims to analyse the management of disability achievements and the factors that support or hinder the development of disability athletes at NPC Makassar City. The achievements made by individuals with disabilities in the field of sports are indeed intriguing to study and examine. The study employed a qualitative research methodology, utilising various data gathering approaches, including observation, interviews, and recording. The research participants included the Head of NPC Makassar City, the Athlete Empowerment Section, the Sports Branch Section, and the Paralympic Athletes. The process of athlete screening is a collaborative effort between SLB sports teachers and the NPC team. The National Paralympic Committee (NPC) monitors the athlete's condition, workplace, and family in order to assess the athlete's progress and achievements. The study's findings suggest that the National Performance Committee (NPC) has the potential to enhance organisational strengthening by means of coordination meetings, facilitating organisations, and executing coaching programmes funded by the regional vernment. The progression of accomplishments among athletes with disabilities NPC assesses SLB for potential athletes and focuses on improving facilities and infrastructure to facilitate achievement coaching, enabling athletes with disabilities to attain success.